Proposal of educational reform (2013)
Given the shortcomings that the Colombian education al system currently presents, it is necessary to consider some possible solutions within the academic curriculum that is present between the first eleven years of basic secondary education. For this purpose we propose the application of a Unified Curriculum that seeks primarily to improve the continuity, and the stimulation of real and non-coercive participation of students through the encouragement of creativity and critical thought.